Incoerenza Dinamica ed Autocontrollo: Proposta per un'Analisi Interdisciplinare - Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
– In the last 25 years, a vast empirical literature has seriously chal- lenged many assumptions on which the standard microeconomic approach is based. Inspired by this evidence, behavioural economics suggests that a research program that integrates the economic, psychological and neuro- scientific literature can provide a theory of human decision-making with stronger descriptive, predictive and normative power. This interdisci- plinary approach does not necessarily imply abandoning the neoclassical modelling tools and losing analytical tractability. As an example, the evo- lution of the economic theory on intertemporal choice is presented, show- ing that some standard economic assumptions can be viewed as special cases in which self-control and dynamic consistency are always guaranteed.
Keywords: 330; Intertemporale Entscheidung; Zeitkonsistenz; Verhaltensökonomik; Theorie